MANAJEMEN HUBUNGAN SEKOLAH DAN MASYARAKAT DI SEKOLAH DASAR - Putri Manafe, Merliana; Aljazira Yasyirulgaza Intifada; Sri Marmoah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
School and community relationship management is one of the important aspects in educational management. This study aims to explain the concept, indicators, best practices, and case studies of school-community relationship management. The method used is library research with a literature review approach. The results show that school-community relationship management is a process of managing communication, cooperation, and partnership between schools and the community carried out in a planned and sustainable manner. Success indicators include the level of community participation, quality of communication, community trust, cooperation with various stakeholders, and positive impact on school development. Best practices show that community involvement through programs such as parenting class, school committees, and school-family-community partnerships has proven effective in improving education quality. The case study at SDIU Al-Khoir Surakarta demonstrates that implementing POAC management functions in school-community relationship management can increase community participation and strengthen school cooperation with its surrounding environment.